Resistensi Masyarakat Urban Dan Masyarakat Tradisional Dalam Menyikapi Perubahan Sosial - Nurdinah Muhammad (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2017)
The impact of globalisation on social change is part of the inevitably global development over time. However, those changes matter when it leads to negative consequences on various aspects such as, people’s identities and cultural values. New values replaced existing deeper-rooted local values, and people aspecially youth develop an identity that gives them a sense of belonging to a global culture instead of their own local identity. Loss of tolerance among each other, changes in patterns of social interaction, lifestyles and fashions are among cultural effects brought by globalization. More than that, information and communication technology has been a principal driver in the spread of globalization. With a new communication technology, ideas can get around the world in just a few moments. These impacts of globalization not only influence cities but as well as villages. Thus, it is important to strengthen the pattern of community defense, both urban and traditional, in the face of unending social changes from the rise of foreign cultures.